Acrylamide in food. (Academic Press, 2023)
Acrylamide in Food, Second Edition, is fully updated with four new chapters that incorporate current literature on acrylamide, including analysis, formation mechanisms, levels in foods, reduction strategies, and new regulations, such as the one made by the European Union in 2017 regarding the presence of acrylamide in processed foods. The book comprises of four parts: part one introduces acrylamide and the food chain in the context of harm and health. Part two focusses on acrylamide in various types of foods, such as bakery products, fried potato products, coffee, battered products, water, table olives, etc. Part three highlights its interaction mechanisms and health effects. Part four discusses methods of analysis. Acrylamide in Food, Second Edition is edited by a team of international experts in the field and is a quality reference in the developing field of acrylamide in food. It is valuable to researchers in the food industry or working on evaluating the factors affecting the formation of acrylamide in different heat-treated foods and the possibilities of reducing acrylamide formation accordingly.